Preparation of a spatial model for rapid prototyping of the upper respiratory tract - Аврунін, О. Г.; Avrunin, O. G.; Nosova, Ya.; Shushliapina, N.; Ibrahim Younouss Abdelhamid (Karlsruhe: NetAkhatAV, 2020)
Preparation of a spatial model for rapid prototyping of the upper respiratory tract is described.The study of full-scale models of the upper respiratory tract allows us to assess the adequacy of mathematical modeling of nasal aerodynamics processes under different breathing conditions and typical pathologies of the nasal cavity, taking into account aspects of individual variability.
Keywords: nasal airways; spatial model; upper respiratory tract; rapid prototyping